Spatial distribution and clustering of contagious caprine pleuropneumonia in goats of Amhara region, Ethiopia - Zegeye, A.; Jemberu, Wudu T.; Fentie, T.; Mekonnen, S.A.; Molla, W. (Elsevier, 2024)
A cross-sectional study with a multistage cluster sampling technique was undertaken from January to July 2019 in Amhara region to identify spatial clusters and distributions of contagious caprine pleuropneumonia (CCPP) hotspots. In the study, a total of 2,080 goats from 258 flocks across 60 villages in 12 districts were tested for CCPP serostatus using Competitive Enzyme-Linked Immunosorbent Assay (C-ELISA). Villages were taken as an aggregate unit to detect spatial distribution and clustering. Spatial autocorrelation, interpolation, and spatial scan statistics analyses were employed to analyze the spatial patterns and clusters of CCPP serostatus. The overall seroprevalence of CCPP at the animal level was 5.1% (95% CI: 3.8-6.6). The spatial distribution of CCPP seropositivity was non-random at the village level (Moran’s I: 0.400791, P-value <0.01). Two statistically significant spatial clusters of CCPP seropositive were found: one in West Gojjam and the other encompassing parts of North Wollo, Oromiya Liyu zone, and South Wollo zones. The CCPP seropositivity showed spatial variation across the Amhara region. High CCPP seropositive spots were found in the southwestern and northeastern parts of the Amhara region. Generally, the findings of this study provide valuable insights in developing disease control strategies, prioritizing target intervention areas and measures, and designating CCPP disease-free zones. Applying movement restrictions and vaccinating goats will be important intervention measures to prevent and control CCPP in the region.